PERANAN KEPUASAN DALAM MEMEDIASI PENGARUH KUALITAS LAYANAN DAN NILAI TERHADAP LOYALITAS PEMUSTAKA PADA UPT PERPUSTAKAAN UNIVERSITAS HALU OLEO KENDARI - Darmawati Darmawati (UPT Perpustakaaan Universitas Hasanuddin, 2017)
The aims of this study were to identify and analyze: (1) The effect of servicequality on customer/user satisfaction. (2). The influence of the quality of services on customer/user loyalty. (3). Influence on customer/user value on satisfaction. (4). Influence customer/user value on customer/user loyalty (5). The influence of satisfaction on customer loyalty. (6) Role customer/user satisfaction in mediatingthe effect of service quality on loyalty customer/pemustaka. (7). ustomer/user role in mediating the effects of customer/user satisfaction value on customer loyalty. This research was conducted at the Library Unit of Halu Oleo University Kendari.The research object is Halu Oleo University student. The number of respondents were 123 persons. Data analysis methods used is SEM (Structural Equation Modeling) using the software AMOS (Analysis of Moment Structural) version 20.The results of this study concluded that: (1). Quality of service has a significanteffect on customer satisfaction (2). Quality of service has a significant effect on user loyalty (3). Value of customer has significant effect on customer satisfaction, (4). Value of customer has significant effect on customer loyalty. (5). Customer satisfaction has significant effect on user loyalty, (6). Customer satisfaction has norole in mediating the effect of service quality on user loyalty (7). Satisfaction of customer has no role in mediating the influence of the value customer loyalty.